2008
DOI: 10.1111/j.1365-313x.2008.03500.x
|View full text |Cite
|
Sign up to set email alerts
|

Defective in Tapetal Development and Function 1 is essential for anther development and tapetal function for microspore maturation in Arabidopsis

Abstract: SummaryIn Arabidopsis, the tapetum plays important roles in anther development by providing enzymes for callose dissolution and materials for pollen-wall formation, and by supplying nutrients for pollen development. Here, we report the identification and characterization of a male-sterile mutant, defective in tapetal development and function 1 (tdf1), that exhibits irregular division and dysfunction of the tapetum. The TDF1 gene was characterized using a map-based cloning strategy, and was confirmed by genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
315
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 298 publications
(327 citation statements)
references
References 41 publications
10
315
1
1
Order By: Relevance
“…However, gapcp1gapcp2 gametes obtained from heterozygous mothers are viable, indicating that the pollen sterility is not due to an alteration in the gamete itself, but to alterations in the cells participating in pollen development in gapcp1gapcp2. Several of the genes controlling tapetum development have been found to affect pollen viability and/or development (Colcombet et al, 2005;Mizuno et al, 2007;Yang et al, 2007;Zhu et al, 2008). The tapetum plays a major role in sporogenesis and is also critical in pollen wall and pollen coat formation (Paxson-Sowders et al, 2001;Dong et al, 2005;Yang et al, 2007).…”
Section: Gapcp Disruption Affects Tapetum Organization and Impairs Pomentioning
confidence: 99%
“…However, gapcp1gapcp2 gametes obtained from heterozygous mothers are viable, indicating that the pollen sterility is not due to an alteration in the gamete itself, but to alterations in the cells participating in pollen development in gapcp1gapcp2. Several of the genes controlling tapetum development have been found to affect pollen viability and/or development (Colcombet et al, 2005;Mizuno et al, 2007;Yang et al, 2007;Zhu et al, 2008). The tapetum plays a major role in sporogenesis and is also critical in pollen wall and pollen coat formation (Paxson-Sowders et al, 2001;Dong et al, 2005;Yang et al, 2007).…”
Section: Gapcp Disruption Affects Tapetum Organization and Impairs Pomentioning
confidence: 99%
“…Transcript levels of AMS, MYB80, and MS1 are significantly reduced in the dyt1 mutant, suggesting that they act downstream of DYT1 (Zhang et al, 2006). Based on analysis of transcript levels within tdf1 and ams mutants, Zhu et al (2008) suggested that TDF1 functions upstream of AMS and that AMS is upstream of MYB80. Xu et al (2010) identified 13 genes as direct targets of AMS using chromatin immoprecipitation, but MYB80 was not among them.…”
Section: Introductionmentioning
confidence: 99%
“…Transcription factors known to be involved in tapetal development include DYSFUNCTIONAL TAPETUM1 (DYT1) (Zhang et al, 2006), MYB33/MYB65 (Millar and Gubler, 2005), DEFECTIVE IN TAPETAL DEVELOPMENT AND FUNCTION1 (TDF1) (Zhu et al, 2008), ABORTED MICROSPORES (AMS) (Sorensen et al, 2003), MALE STERILITY1 (MS1) (Wilson et al, 2001;Ito and Shinozaki, 2002) and MYB80 (formerly MYB103) (Higginson et al, 2003;Li et al, 2007;Zhang et al, 2007). DYT1 and AMS both encode basic-helix-loop-helix proteins, whereas TDF1 and MS1 encode MYB and PHD transcription factors, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Several transcriptional regulators have been reported to be associated with tapetal degeneration, including Arabidopsis MYB33/MYB65 4 , DYSFUNCTIONAL TAPETUM1 (DYT1) 5 , DEFECTIVE IN TAPETAL DEVELOPMENT AND FUNCTION1 (TDF1) 6 , ABORTED MICROSPORE (AMS) 7 , MALE STERILITY1 8 , rice GAMYB 9 , UNDEVELOPED TAPETUM1 10 , TAPETUM DEGENERATION RETARDATION (TDR) 11 , PERSISTENT TAPETAL CELL 1 (PTC1) 12 , and APOPTOSIS INHIBITOR5 (API5) 13 . However, mechanisms by which these regulators regulate tapetal PCD remain unclear.…”
mentioning
confidence: 99%